Effects of Chiari osteotomy on acetabular development in the growing subject. Experimental study in puppies - Bitan, F; Duriez, J; Egozcue, R; Flautre, B; Morel, G; Morin, C (International orthopaedics, 1989)
A Chiari osteotomy was performed on 10 dogs aged 2 months in order to assess the risks of mechanical or ischaemic loss of growth potential in the peri-acetabular cartilage. The development of the acetabular roof was studied by radiographs, microradiographs and histological assessment between 2 and 12 months. Apart from a few mechanical complications, the principal findings were the absence of any signs of necrosis, persistence of a strongly osteoblastic roof and readaptation of the trabecular pattern with articular remodelling, provided the mechanical conditions were satisfactory. The osteotomy must be sufficiently low, while remaining extra-articular, and adequate medial shift must be obtained. The interposed capsular tissue can then become dense and fibrous, providing a sliding surface.